Louis Jay Hazam papers - Hazam, Louis Jay, 1911-1983.
Correspondence, writings, scripts, biographical material, scrapbook, printed matter, and other papers relating to Hazam's career as a writer for radio and television and as a producer of television documentaries for the National Broadcasting Company.
Television producer and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: National Broadcasting Company; Documentary television programs; Radio programs; Radio scripts; Television programs; Television scripts; Authors; Television producers